Peran Dakwah KH. Choer Affandi Pendiri Pesantren Miftahul Huda Manonjaya di Indonesia : Perspektif Sejarah, Politik dan Pendidikan - Tatang Hidayat; Syahidin Syahidin; Istianah Istianah (Tarikh : Journal of Islamic History and Civilization, 2026)
The purpose of this study is to analyze the role of the da’wah of KH. Choer Affandi, founder of the Miftahul Huda Manonjaya Islamic boarding school in Indonesia, from historical, political, and educational perspectives. This study employs a qualitative approach and descriptive methods. The research findings indicate that the history of the establishment of the Miftahul Huda Manojaya Islamic Boarding School began with KH. Choer Affandi’s experience with political Islam, which started while he was a student at the Sukamanah Islamic Boarding School led by KH. Zainal Musthafa, and the Gunung Puyuh Islamic Boarding School led by KH. Ahmad Sanusi. The DI/TII was a historical event in the journey of the Indonesian nation that has long been viewed by the Unitary State of the Republic of Indonesia as a “rebellion.” In explaining Choer Affandi’s biography, one must inevitably address the DI/TII event. After K.H. Choer Affandi came down from the mountains, his method of struggle eventually shifted toward education through the establishment of an Islamic boarding school. This marked the turning point in Choer Affandi’s struggle: from the initial “jihad bil qital” (struggle through combat) by taking up arms in the mountains, it shifted to “jihad bil fikroh” (struggle through thought), where he assumed the role of a scholar as the “Warasatul Anbiya” (heir to the prophets). The Miftahul Huda Islamic Boarding School was founded on August 7, 1967, by K.H. Choer Affandi. Since its establishment in 1967, the Miftahul Huda Islamic boarding school has had a significant social and religious impact on the community of Manonjaya, Tasikmalaya Regency. KH. Choer Affandi met Buya Hamka and M. Natsir while performing the Hajj in 1974. KH. Choer Affandi’s role in da’wah extended beyond the local community of Tasikmalaya—where he initiated the establishment of the Tasikmalaya Islamic Hospital—and was undeniably significant on the national stage as well. KH. Choer Affandi was one of the founders of the West Java Islamic Boarding School Cooperation Agency (BKsPP). Later, Pondok Gontor, Diniyyah Putri Padang Panjang, and others joined, so that the BKsPP, which initially covered West Java, became a national organization known as the Indonesian Islamic Boarding School Cooperation Agency (BKsPPI).